Component-based system design: analytic real-time interfaces for state-based component implementations - Lampka, Kai; Perathoner, Simon; Thiele, Lothar (International journal on software tools for technology transfer, 2013)
Compositionality can be a helpful paradigm for coping with the complexity of large embedded systems with real-time constraints. This article exploits state-less assume/guarantee real-time interfaces extended by component properties, both to be satisfied invariantly by any component implementing the respective interface. This supports compositional evaluation of system designs, as overall properties of the latter can be derived from the component interfaces, rather than verifying them for the complete system model at analysis time. Moreover, our design strategy based on extended analytic real-time interfaces features an incremental, and component-wise development of (heterogeneous) system designs. This is, because the interface-derived properties of an overall system design are proven to be invariant under composition and substitution of interfaces and components, as long as the interface definitions are consistent, the (potentially heterogeneous) components implement their interfaces, and a dedicated inclusion criterion holds. This article develops the machinery for deriving analytic interface descriptions from Timed Automata-based component models. It develops the required consistency and conformance tests for deciding the aforementioned invariance of interfaces and components with respect to composition and substitution. This way we hope to advocate a strictly compositional design approach and improve the scalability of state-based analysis methods which we investigate in several case studies.